Réponses

2014-02-08T22:53:52+01:00
A=(x+2)(-2x-3)+x+2=(x+2)(-2x-3+1)=(x+2)(-2x-2)=-2(x+2)(x+1)

B=-(x+2)^2+3(x+2)(-x+1)+5(x+2)=(x+2)(-(x+2)+3(-x+1)+5)=(x+2)(-x-2-3x+3+5)=(x+2)(-4x+6)=2(x+2)(-2x+3)

C=(t+1)(-2t+3)-2(t+1)^2+(t+1)(3t+4)=(t+1)(-2t+3-2(t+1)+3t+4)=(t+1)(-2t+3-2t-2+3t+4)=(t+1)(-t+5)

D=(x+3)(2x+1)+(2x+6)(-5x+1)=(x+3)(2x+1)+2(x+3)(-5x+1)=(x+3)(2x+1+2(-5x+1))=(x+3)(2x+1-10x+2)=(x+3)(-8x+3)

E=(x-1)^2+2(-x+1)(x+3)=(x-1)^2-2(x-1)(x+3)=(x-1)(x-1-2(x+3))=(x-1)(x-1-2x-6)=(x-1)(-x-7)=-(x-1)(x+7)
  • Omnes
  • Modérateur confirmé
2014-02-08T22:54:24+01:00